Did the Euro Crisis Affect Non-Financial Firm Stock Prices Through a Financial or Trade Channel? - Claessens, Stijn (IMF Working Papers; Working Paper ;, 2011)
This paper analyzes through what channels the euro crisis has affected firm valuations globally. It examines stock price responses over the past year for 3045 non-financial firms in 16 countries to three key crisis events. Using pre-crisis benchmarks, it separates effects arising from changes in external financing and trade conditions and examines how bank and trade linkages propagated effects across borders. It finds that policy measures announced impacted financially-constrained firms more, particularly in creditor countries with greater bank exposure to peripheral euro countries. Trade linkages with peripheral countries also played a role, with euro exchange rate movements causing differential effects.